Granulocyte Colonies Derived from Lymphocyte Fractions of Normal Human Peripheral Blood - Zucker-Franklin, D. (1974)
Granulocyte colonies can be grown from leukocyte-rich plasma obtained from normal human peripheral blood. Purification of lymphocytes by the Ficoll-Hypaque gradient method and subsequent removal of monocytes achieved a 10-fold increase in the number of colonies formed, suggesting that the colony-forming cell is nonadherent, nonphagocytic, and morphologically difficult to distinguish from a lymphocyte. Ultrastructural analysis of intact colonies by a new method developed for this purpose showed orderly differentiation and maturation. Only undifferentiated cells were seen in colonies on day 5, promyelocytes with developing primary lysosomes were present on day 9, whereas myelocytes and metamyelocytes were most prevalent on days 15 and 21, respectively. The studies suggest where further concentration of precursor cells may be attempted, and where further functional and histochemical analysis of colonies on the ultrastructural level will be possible.